Penerapan Material Flow Cost Accounting (MFCA) Dan Akuntansi Manajemen Lingkungan Untuk Pengurangan Limbah Dan Peningkatan Kinerja Lingkungan - Panggabean, Solomon Slow; Doloksaribu, Ardin; Rajagukguk, Rahel Rut Syeba; Sihaloho, Esra Sparia; Sagala, Agnes Agustina (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to analyze waste reduction and environmental performance improvement after the implementation of Material Flow Cost Accounting (MFCA) and Environmental Management Accounting. The type of research method used in writing this scientific work is the literature study method. The results of this study indicate that Material Flow Cost Accounting can assist companies in identifying and optimizing processes that have the potential to generate waste, thereby minimizing negative impacts on the environment and improving environmental performance. The company can build public and stakeholder trust in the company's business practices requiring transparency in environmental management through MFCA. Companies in implementing MFCA will show their concern for the environment and can support the sustainability of the company to continue to innovate and gain profits in the company.